Assessing stress and its causes among postgraduate prosthodontics students - Almabadi, Afaf A. (Frontiers in Education, 2025)
IntroductionStress is a widespread but multifactorial phenomenon, and dental students are known to experience particularly high levels of perceived stress. While this problem has been extensively studied in undergraduate dental students, there are little data on perceived stress in postgraduate prosthodontic residents. The objective of this study was to assess common potential stress, together with contributing factors, in postgraduate students attending the Prosthodontics Department at King Abdulaziz University Faculty of Dentistry (KAUFD), Jeddah, Saudi Arabia.Materials and methodsThis was an initial exploratory study of perceived stress and contributing factors in postgraduate students to inform future wide-scale investigations. In this cross-sectional study, an electronic survey was distributed to postgraduate students in the Prosthodontics Department at KAUFD to collect demographic data and perceived levels of stress as assessed by a modified form of the Dental Environment Stress Scale (DES). Statistical analysis was performed using RStudio (R v4.3.0).ResultsThirty-five postgraduate students participated in this study. Academic overload (62.9%) and fear of failure (51.4%) were most commonly reported as causing severe stress in participants. There were no statistically significant differences in commonly reported severe stress (≥40%) according to gender, year of study, or previous experience (all p > 0.05), However, examination and grading and fear of failure resulted in a higher level of perceived stress in female than male students, and academic overload and requirements produced more stress in students without previous qualifications. Previous experience duration was associated with completing examination requirements and fear of failure domains (Bonferroni-corrected q-values of 0.045 and 0.003, respectively). Nevertheless, as the study was relatively small and conducted in a single institution using a self-reported questionnaire, the results must be cautiously interpreted.ConclusionThis exploratory pilot study reveals that postgraduate dental students experienced high levels of stress. Periodic assessment of perceived stress levels and possible causative stressors is recommended in academic settings, with the DES a valid instrument for this purpose. Our data are useful for formulating future recommendations on stress management workshops and awareness campaigns within academic curricula at dental schools. However, the findings of this study must be regarded as preliminary and warrant large-scale confirmation to establish generalizability.